Tradisi Ma’sanro in the Life of the Bugis Community of Bulukumba Regency - Firzah Aurelia; Abdul Rahman (Ridwan Institute, 2021)
The research was made with a view to know and understand ma’ sanro traditions that made by the bugis community in Bulukumba district. Ma 'sanro himself is one of the traditions that have so far been practiced by the bugists in the fur district whose original purpose was to treat the sick with a variety of ancient plants or spices in which there was no medical science at the time. At present, however, ma 'sanro is not only used for medicine but has begun to be a tradition that has always been associated with the customs of the bug bug society. The study is one whose data uses qualitative data. His data collection techniques are conducted by observation, interview and reference collection related to ma 'sanro traditions in society. As for his research, ma 'sanro is a tradition believed by the populace to treat the sick. But now, over time sanro has been used not only to treat diseases but also to other matters such as home entry traditions, the use of black magic and so on that are now part of a community belief